Reading Hizb Ghozali In Boarding School Luqmaniyyah Yogyakarta - Rahmanto, Oki Dwi (UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
Abstract Reading Hizb Ghozali in Pondok Pesantren Luqmaniyyah Yogyakarta Hizib Ghozali is one of the many benefits of Hizb. As for the practice, Santri must do the Tirakat. Besides, Tirakat of Santri is obliged to do readings Hizib Ghozali every day. If Santri violates will be punished by the caretaker of Pesantren Luqmaniyyah Yogyakarta. By using Karl Mannheim's Sociology of knowledge theory, it is hoped that this research could reveal meaning the Santri in the reading of Hizb Ghozali. Karl Mannheim discusses in detail the behavioural behaviour and meaning of human behaviour. Karl Mannheim distinguishes between three different meanings in social action, i.e. objective, expressive and documentary meaning. As for the results of this research, the objective meaning contained in the reading Hizb Ghozali in Pondok Pesantren Luqmaniyyah is reading Hizib Ghozali is a form of Ijazahan from Kyai Na'im as caretaker of Pesantren Luqmaniyyah, besides, the recitation of Hizb Ghozali believed to grant all the Hajat desired. The meaning of expressive is the recitation of Hizb Ghozali performed by the students because of the sense of Ta'dzim on the teacher and can be trusted to give many benefits. The meaning of the documentary in the reading of Hizb Ghozali is the recitation of Hizb Ghozali in Pondok Pesantren Luqmaniyyah Yogyakarta is a practice that can be a thorough culture.. Keywords: Hizib Ghozali, Karl Mannheim's, Sociology of knowledge theory. Abstrak Membaca Hizib Ghozali dalam Pondok Pesantren Luqmaniyyah Yogyakarta, Hizib Ghozali adalah salah satu banyak manfaat dari Hizib. Adapun prakteknya, Santri harus melakukan Tirakat tertentu. Selain itu, Tirakat Santri wajib melakukan pembacaan Hizib Ghozali setiap hari. Jika Santri melanggar akan dihukum oleh penjaga Pesantren Luqmaniyah Yogyakarta. Dengan menggunakan Karl Mannheim tentang ilmu pengetahuan teori, diharapkan bahwa penelitian ini dapat mengungkapkan makna Santri dalam membaca Hizb Ghozali. Karl Mannheim membahas secara rinci perilaku dan makna perilaku manusia. Karl Mannheim membedakan antara tiga makna berbeda dalam aksi sosial, seperti makna, ekspresif dan dokumenter. Adapun hasil penelitian ini, tujuan yang terkandung dalam membaca Hizb Ghozali di Pondok Pesantren Luqmaniyyah adalah bentuk dari Ijazahan dari Kyai Na'im sebagai pengurus dari Pondok Pesantren Luqmaniyyah. Makna ekspresif pembacaan Hizib Ghozali dilakukan oleh Santri karena rasa takdzim pada Kyai dan dapat dipercaya untuk memberikan banyak keuntungan. Makna dari film dokumenter dalam pembacaan dari Hizib Ghozali adalah pembacaan dari Hizb Ghozali di Pondok Pesantren Luqmaniyyah Yogyakarta adalah latihan yang dapat menjadi budaya menyeluruh. Kata Kunci : Hizib Ghozali, Karl Mannheim, Sosiologi Teori Pengetahuan.